Un camí de setanta-cinc fites (Evolución bibliomètrica de la revista Cuadernos de Geografía, 1964-2003) - Enric Ramiro Roca (Investigaciones Geográficas)
The article refl ects the evolution of the magazine Notebooks of Geography that edits the University of Valencia from 1964. After an introduction and the current condition(state) on the bibliographical studies in general and on the social sciences especially, there are done an analysis of the origin and stages of the Valencian magazine. Later it is investigated on the aturoes and his(her,your) most signifi cant characteristics as the degree of presencialidad, the type of authorship, the degree of collaboration of those who write, dedicating an espeical attention to the study of the kind(genre). The third block centres on the contents of the publication and the variables as the territorial area that they treat, you are afraid of them and his(her,your) language, as well as the references bibliogafi cqas and the initial summaries. For last, there are marked a few conclusions and a few offers of future